Revising the shock classification of meteorites. (6th March 2017) - Fritz, Jörg; Greshake, Ansgar; Fernandes, Vera A.
Abstract: The current shock classification scheme of meteorites assigns shock levels of S1 (unshocked) to S6 (very strongly shocked) using shock effects in rock‐forming minerals such as olivine and plagioclase. The S6 stage (55–90 GPa; 850–1750 °C) relies solely on localized effects in or near melt zones, the recrystallization of olivine, or the presence of mafic high‐pressure phases such as ringwoodite. However, high whole rock temperatures and the presence of high‐pressure phases that are unstable at those temperatures and pressures of zero GPa (e.g., ringwoodite) are two criteria that exclude each other. Each type of high‐pressure phase provides a minimum shock pressure during elevated pressure conditions to allow the formation of this phase, and a maximum temperature of the whole rock after decompression to allow the preservation of this phase. Rocks classified as S6 are characterized not by the presence but by the absence of those thermally unstable high‐pressure phases. High‐pressure phases in or attached to shock melt zones form mainly during shock pressure decline. This is because shocked rocks (<60 GPa) experience a shock wave with a broad isobaric pressure plateau only during low velocity (<4.5 km s −1 ) impacts, which rarely occur on small planetary bodies; e.g., the Moon and asteroids. The mineralogy of shock melt zones provides information on the shape and temporal duration of the shock wave but no information on the general maximum shock pressure in the whole rock.